Movement and migration of flathead mullet Mugil Cephalus in a warm temperate South African estuary - Mukhari, Dinah Lorraine (https://orcid.org/0000-0001-7558-4360) (Rhodes University, 2026)
The global decline of estuary-associated fish species is largely attributed to anthropogenic impacts, including overexploitation, habitat modification and altered flow, and thermal regimes driven by climate change. The flathead mullet Mugil cephalus is an estuary-associated cosmopolitan species of high fisheries value, and plays a crucial role in aquatic estuarine food webs. Despite this, little is known about their movement patterns in estuaries, particularly on the African continent, and how these movements may be affected by a changing climate, which in turn will impact fisheries and the presence of predators who feed on them. As such, we used acoustic telemetry, thermal tolerance laboratory experiments and otolith microchemistry to gain a better understanding of movements and habitat connectivity of M. cephalus linked to changes in temperature. Acoustic telemetry was used to monitor the fine-scale habitat use of M. cephalus for a period of one year between March 2023 and April 2024 in the warm temperate permanently open Kowie Estuary, South Africa. Results revealed extensive estuary use, with significant individual variation in movement patterns, ranging from high residency to the estuary exhibited by half of population to high levels of connectivity between the estuary and adjacent marine environment by the other half. Movement patterns also changed seasonally, with fish exhibiting high levels of activity and utilising the entire length of the estuary during austral summer, and being absent in the upper reaches of the estuary during austral winter. Linear Mixed-effects Models (LMM) showed that river flow and both sea and river water temperature significantly affected the daily average position of fish in the estuary. Periods of increased freshwater flow and decreased river temperatures led to downstream movements by most individuals from the upper reaches to the lower-middle reaches; however, despite the downstream movement, fish did not move into the mouth region and marina, which could be attributed to the cooler sea water, particularly during summer. Thermal tolerance experiments aligned with the movements observed in the wild. Despite the revealed broad upper and lower critical thermal limits (CTmin = 3.2 °C; CTmax = 37.7 °C), thermal stress (identified by breakpoints in ventilation rates) was experienced at temperatures above and below critical limits (13.5 and 29.3 °C). Water temperatures in the upper reaches of the Kowie Estuary during austral winter dropped below the lower critical limit, suggesting that thermal constraints play a significant role in shaping habitat use and seasonal distribution of M. cephalus in warm temperate estuaries. Using Random Forest machine learning, otolith microchemistry results (Sr:Ca, Ba:Ca, Mg:Ca, Rb:Ca and Mn;Ca) showed that the spatial and temporal movement patterns and seasonal drivers of this species into and out of the Kowie Estuary are consistent throughout their lifetime, from larval estuarine recruitment to moving to the marine environments during winter season. Furthermore, the combined acoustic telemetry and otolith microchemistry results revealed substantial individual variation in movement behaviour and responses to environmental conditions, thus supporting a condition-dependent framework for partial migration, whereby inter-individual differences in thermal tolerance, such as greater tolerance to warmer or cooler waters may directly influence the likelihood of an individual becoming migratory or resident. Framed within the movement ecology paradigm, these findings underscore the role of internal state (e.g., physiological thresholds) interacting with external drivers (e.g., temperature, flow) in shaping movement decisions and connectivity patterns of estuary-associated species such as M. cephalus. Both intra-and inter-seascape connectivity of the Kowie Estuary and the adjacent marine environment is crucial for the persistence of M. cephalus especially under the growing human and climate pressures which are expected to intensify and alter estuarine ecosystems. The results of this study underscores the importance of a multimethod approach, combining fine scale and lifetime habitat connectivity data with environmental drivers to understand the mechanisms underlying fish movement across dynamic estuarine and marine environments.
Keywords: Underwater acoustic telemetry (http://id.loc.gov/authorities/subjects/sh2001002971); Climatic changes (http://id.loc.gov/authorities/subjects/sh85027037); Estuarine fishes -- South Africa (http://id.loc.gov/authorities/subjects/sh95000489); Striped mullet (http://id.loc.gov/authorities/subjects/sh85088272); Otoliths -- Analysis (http://id.loc.gov/authorities/subjects/sh85096060); Thermal tolerance (Physiology) (http://id.loc.gov/authorities/subjects/sh2012001084); Ichthyology